Study of Stress Degradation Behavior of Rasagiline Mesylate Under Hydrolytic Conditions by High Performance Liquid Chromatography - Shelke, P. G.; Chandewar, A. V. (Drug Research, 2014)
A precise and rapid reverse phase HPLC method has been developed for the estimation of Rasagiline Mesylate in bulk drug under stressed hydrolytic conditions according to ICH guidelines Q1(A)R2. The stressed samples of Rasagiline Mesylate were analyzed using Prontosil ODS column. The mobile phase consists of methanol and Phosphate buffer. The pH of the phosphate buffer was adjusted to 3.0 using orthophosphoric acid. The composition of mobile phase Methanol: Phosphate buffer (75:25 v/v) was kept constant up to 1 minute and then changed to 90:10 v/v in next 9 min by HPLC gradient programming. The flow rate was maintained at 1.0 ml/min and detection was carried out at 210 nm using 996 PDA detector. The method was validated in terms of linearity, accuracy, precision specificity and selectivity. The method was found to be linear in the range of 5–15 µg/ml with a correlation coefficient of 0.993.
Keywords: chemistry; drug research; neurological disorders